Major principles of media law - Overbeck, Wayne (Holt, Rinehart, and Winston, 2008)
MAJOR PRINCIPLES OF MEDIA LAW is a comprehensive and concise summary of media law. The text offers a lawyer's grasp of current cases and a teacher's grasp of the key principles of communication law. The text is revised every year to include the most recent developments in communication law through the end of the Supreme Court's term. Each August, a new edition is available for fall classes, with recent developments through July 1 fully integrated into the text, not added as an appendix or separate supplement